Usefulness of 18F-FDOPA PET for the management of primary brain tumors: a systematic review of the literature - Somme, François; Bender, Laura; Namer, Izzie Jacques; Noël, Georges; Bund, Caroline (Cancer imaging, 2020)
Contrast-enhanced magnetic resonance imaging is currently the standard of care in the management of primary brain tumors, although certain limitations remain. Metabolic imaging has proven useful for an increasing number of indications in oncology over the past few years, most particularly 18 F-FDG PET/CT. In neuro-oncology, 18 F-FDG was insufficient to clearly evaluate brain tumors. Amino-acid radiotracers such as 18 F-FDOPA were then evaluated in the management of brain diseases, notably tumoral diseases. Even though European guidelines on the use of amino-acid PET in gliomas have been published, it is crucial that future studies standardize acquisition and interpretation parameters. The aim of this article was to systematically review the potential effect of this metabolic imaging technique in numerous steps of the disease: primary and recurrence diagnosis, grading, local and systemic treatment assessment, and prognosis. A total of 41 articles were included and analyzed in this review. It appears that 18 F-FDOPA PET holds promise as an effective additional tool in the management of gliomas. More consistent prospective studies are still needed.